Ascensão e virtude em Plotino - Bernardo Guadalupe dos Santos Lins Brandao (2012)
Plotinus' philosophy is not only a sistematized discursive thought, with doctrines and arguments, but also a way of life, in which virtue and contemplation have an important role. The central aspect of this way of life is the notion of ascension: according to Plotinus, philosophy can be ajourney to the Intellect and the One. In this research, I analyze the relation between ascention and virtue in the Enneads, trying to understand howcan virtue influence the philosophical contemplation and identify the methods employed in the journey.